Analisis Konsentrasi SO2, NO2 dan Partikulat pada Sumber Emisi Tidak Bergerak (Cerobong) Berbahan Bakar Batubara dan Cangkang (Studi Kasus di Kabupaten Muaro Jambi) - Sugiarto Sugiarto; Peppy Herawati; Anggrika Riyanti (Jurnal Daur Lingkungan, 2019)
The palm oil processing industry in which produces Crude Palm Oil (CPO) generally uses boilers. The combustion process with a boiler will produce pollutants in the form of particulates (dust), and gases such as NO2 and SO2. There are two palm oil processing industries in Muaro Jambi District that use different fuels: coal and oil palm shell. The purpose of this study was to determine the ratio of SO2, NO2 and particulate concentration in industries that use coal and oil palm shell.  Primary data taken in the form of concentrations of SO2, NO2 and particulates also meteorological data. Secondary data taken in the form of map area, height and diameter of the boiler, and production capacity. Sampling time is in the morning, afternoon and evening which is repeated in 3 times. The results showed that the comparison of NO2 and SO2 concentrations produced from coal-fired boilers was higher than shell-fired boilers, but both were still below the quality standard. Particulate concentrations in the palm oil processing industry that use coal-fired boilers are above the quality standard, while shell-fired boilers still meet quality standards.